2022
DOI: 10.1111/bcp.15253
|View full text |Cite
|
Sign up to set email alerts
|

Can nebulised HepArin Reduce morTality and time to Extubation in patients with COVID‐19 Requiring invasive ventilation Meta‐Trial (CHARTER‐MT): Protocol and statistical analysis plan for an investigator‐initiated international meta‐trial of prospective randomised clinical studies

Abstract: There is significant interest in the potential for nebulised unfractionated heparin (UFH), as a novel therapy for patients with COVID‐19 induced acute hypoxaemic respiratory failure requiring invasive ventilation. The scientific and biological rationale for nebulised heparin stems from the evidence for extensive activation of coagulation resulting in pulmonary microvascular thrombosis in COVID‐19 pneumonia. Nebulised delivery of heparin to the lung may limit alveolar fibrin deposition and thereby limit progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…LMWH administered by nebulization was found effective in protecting human nasal cells from infection with SARS-CoV-2, suggesting its possible prophylactic use [ 83 ]. Clinical trials of nebulized heparin in COVID-19 treatment are currently under way in several countries [ 11 , 12 , 13 , 84 ].…”
Section: Non-anticoagulant Action Of Heparin and Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…LMWH administered by nebulization was found effective in protecting human nasal cells from infection with SARS-CoV-2, suggesting its possible prophylactic use [ 83 ]. Clinical trials of nebulized heparin in COVID-19 treatment are currently under way in several countries [ 11 , 12 , 13 , 84 ].…”
Section: Non-anticoagulant Action Of Heparin and Sepsismentioning
confidence: 99%
“…Investigations have also shown that binding of heparin to SARS-CoV-2 spike proteins may inhibit virus infectivity [ 9 , 10 ]. Indeed, clinical trials with nebulised heparin exploring the anti-inflammatory and anti-viral properties of heparin are ongoing [ 11 , 12 , 13 , 14 ]. Recent advances in heparin research indicated that heparin not only interacts with the coagulation cascades, but also with blood cells and numerous components of the complement system thereby influencing the innate immune responses to infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has already been tested for heparin. 44 The starting material is derived from pentosan, a plant-derived polysaccharide xylan with a well-defined repeating structure 19 and, even following a chemical sulfation step, it remains highly homogeneous, making it easier to ensure both consistency and to avoid contamination; two problems that have dogged heparin production in recent years. 45,46 What is known about this topic?…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ideally, more time frame is required to follow the trend as these inflammatory markers take time to resolve our findings are in line with those from the published literature and clinical experience, which show that inhaled nebulized unfractionated heparin (UFH) is very safe for patients with a wide variety of respiratory diseases. 4 , 5 …”
mentioning
confidence: 99%